Penerapan Budaya Positif untuk Penguatan Pendidikan Karakter di Kelas X SMA Negeri 1 Sooko - Syafila Chabsarotul Islamiyah; Timurrana Dilematik; Qonita Annavidza; Nuril Badiatus Sa’adah; Ika Ayuningsih; Farah Annisa (Jurnal Bintang Pendidikan Indonesia, 2024)
This research was conducted to see the influence of the positive culture implemented in schools on improving the character education of class X students at SMAN 1 Sooko Mojokerto. The research method used in writing this article is descriptive qualitative. The population of this study was all class X students at SMAN 1 Sooko by random sampling in class X-6. The researcher applied calculations, the greater the score on the student's character education instrument, the more the application of positive culture influenced the action. In this case, the data we use is taken from student character education questionnaires and direct observation. Based on the results of the research we conducted in class X-6, positive culture has a quite significant influence on student character education. This proves that the positive culture implemented at SMAN 1 Sooko has been successful and has become the basis for forming the character of students with the profile of Pancasila students in accordance with the current curriculum.